Some Properties of Fuzzy q-open Set and Fuzzy q-b Open Set in Fuzzy Quad Topological Space - Ranu Sharma; Bhagyashri A. Deole; Smita Verma (Recent Advances in Mathematical Research and Computer Science Vol. 10, 2022)
Any non-empty set with four topologies is called a Quad topological space. Let X be a non-empty universal set. A fuzzy set \(λ\) : X \(→\) [0,1] is a mapping from X into the unit interval I = [0,1], x \(ε\) X for all . The purpose of this paper is to define the concept of fuzzy q-open set and fuzzy q-b open sets in fuzzy quad topological space .We describe some of the basic operations on fuzzy q-open sets and fuzzy q-b open sets. Furthermore, we discuss the properties of fuzzy q- continuous function and fuzzy q-b continuous function. we introduce the concept of fuzzy q-gb open sets and study fuzzy q-separation axioms and fuzzy q-b separation axioms in fuzzy quad topological space.